1987
DOI: 10.1172/jci112804
|View full text |Cite
|
Sign up to set email alerts
|

Different hematologic phenotypes are associated with the leftward (-alpha 4.2) and rightward (-alpha 3.7) alpha+-thalassemia deletions.

Abstract: We have compared the phenotypes of the two common deletion forms of a'-thalassemia by analysis of umbilical cord blood samples from Melanesia. Homozygotes for the leftward, 4.2-kilobase, deletion (-a4-2) had significantly higher levels of Hb Bart's at birth than homozygotes for the rightward, 3.7-kilobase, deletion (-a3')

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
2

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 29 publications
2
20
2
Order By: Relevance
“…This distinction in allele frequency observed amongst ethnic Chinese consolidates our previous finding [7] and is in accordance with the findings of other similar studies on the local population [11]. In general, the α – 3.7 single gene deletion has a global distribution among all ethnic groups, and is especially prevalent in most tropical and subtropical populations studied [12]. …”
Section: Resultssupporting
confidence: 91%
“…This distinction in allele frequency observed amongst ethnic Chinese consolidates our previous finding [7] and is in accordance with the findings of other similar studies on the local population [11]. In general, the α – 3.7 single gene deletion has a global distribution among all ethnic groups, and is especially prevalent in most tropical and subtropical populations studied [12]. …”
Section: Resultssupporting
confidence: 91%
“…In this context, it should be noted that heterozygotes for nondeletion defects usually manifested the «-thalassemia carrier phenotype, whereas persons with a single a-globin gene deletion have either silent carrier phenotype or ex press very mild thalassemia-like hematological manifes tations [19,20]. These findings may be explained on the ba sis of recent studies which demonstrated that: (a) the « 2-globin gene produces 2-3 times more a-globin chains as compared to the «r globin gene [21], and (b) the remaining a-globin gene in the rightward deletion (-a 3-7), but not in the leftward (-a 4,2), shows a compensatory increase around 1.8 times of the a-globin chain output [22][23][24]. Fur thermore a-globin production during in vitro translation of reticulocyte RNA and during labelling of intact reticu locytes was less significantly depressed in HbH disease pa tients with a combination of a deletion defect and an ini tiation codon mutation of the a,-gene than in the patients with a similar initiation codon mutation (a ,hala) of the a 2- gene [18].…”
Section: Discussionmentioning
confidence: 99%
“…Such a phenomenon is not demonstrated in the –α 4.2 kb deletion [5, 6]. Deletional α-thals are more common than the nondeletional types.…”
Section: Introductionmentioning
confidence: 99%